KNOW-HOW REALITY WITH THE METHODS AND FEATURES OF ACCOUNTING SCIENTIFIC RESEARCH : “AN EXPLORATORY STUDY FROM THE POINT OF VIEW OF FACULTY MEMBERS IN THE ACCOUNTING DEPARTMENTS OF THE LIBYAN ACADEMY AND THE FACULTIES OF ECONOMICS AT SABRATHA AND AL-ZAWIYA UNIVERSITIES” - الرك حامد مولود علي (Tobruk University Journal of Social and Human Sciences, 2023)
The study aims to shed light on the methods of accounting scientific research, and the reality of the knowledge and know-how of researchers in accounting sciences with the features of scientific research methods. The researcher used the analytical descriptive approach by examining specialized books, periodicals and scientific journals. A questionnaire consisting of four parts was designed, the first part was data on the study sample, and the second part consisted of 10 paragraphs to cover the accounting scientific research methods, and its purpose. The third part consists of 10 paragraphs to cover the features of accounting scientific research methods. Where 84 questionnaires were distributed to faculty members and postgraduate students in the Accounting Department of the Libyan Academy for Postgraduate Studies, and the faculties of Sabratha and Al-Zawiya universities. 64 valid questionnaires were received that is, by 74.4% of the distributed questionnaires, Its data was analyzed using appropriate statistical methods, which showed that the study sample had very good knowledge and know-how of scientific research methods and their purpose. And a very good knowledge and know-how of the features of scientific research methods.